Post-graffiti in Lisbon: on spatial localization and market absorption - Revi, Rohit (2017)
Graffiti-making has been historically well located within the politics of territoriality/ transgression, deindustrialization/ decline, appropriation/ affirmation and other such inter-related frameworks. Such historicizations exist in parallel to a history of institutionalization of graffiti-making, leading up to the first emergence of the phrase post-graffiti in the discourse. The post-graffiti has alternatively and independently also been used to describe an empirically observed shift in graffiti-making practices; from the typographical to the iconographical. In this context, the operationalization of a set of urban intervention policies by the Lisbon City Council provide an interesting inroad into the processes that underlie the market absorption of graffiti. Through a field analysis of street art in Lisbon as well as an examination of the intervention policy and its consequences, this paper presents that the intervention policies and associated public rhetoric manufactured a binary of order-disorder within the practices of graffiti-making, enabling graffiti and graffiti-making practices in Lisbon to be spatially localized. Such spatial localization, in turn, facilitated market activities surrounding graffiti. For the graffiti and the graffiti-makers, state/administrative sanction and the emergence of market activities meant heightened security, safety and a greater audience field – conditions that made iconographical aesthetics a virtue and a greater necessity. Thus, the post-graffiti shift in aesthetics has to be understood within the context of institutionalization of street art enabled by urban interventions and contemporary capitalism.